Mummies in the morning - Osborne, Mary Pope. (New York : Random House, 1993)
Jack and his younger sister take a trip in their tree house back to ancient Egypt, where they help a queen's mummy continue her voyage to the Next Life.
"A First stepping stone book."
Keywords: Time travel; Mummies; Magic; Tree houses